Time series analysis of solar radiation in the City of Recife/PE (Research, Society and Development, 2020)
Objective: analyze and describe the best fit for time serie of solar radiation in the city of Recife/PE, applying the ARMA and ARMAX models, in addition to forecasting radiation levels for the next six years. Method: used climate series data of the National Institute of Meteorology (INMET), available from January 2009 to December 2018. The comparison of the models was performed by Akaike's information criteria. Results: the series of solar radiation presents a high variability of the monthly averages, indicating the presence of seasonality and a strong negative asymmetry. The results of the error statistics show the accuracy of the ARMAX model (2.1), with a percentage error close to 18.68%, comparing the observed and adjusted series, in addition, it was possible to identify that the forecast manages to capture the existence seasonality. Conclusion: ARMAX model was adequate to describe a solar radiation including exogenous variables, being a tool capable of assisting in public health policies in the fight against skin cancer and interventions.